2018
DOI: 10.1371/journal.pone.0204033
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling reveals that a MYB transcription factor MsMYB4 contributes to the salinity stress response of alfalfa

Abstract: MYB transcription factors are important regulators of the plant response to abiotic stress. Their participation in the salinity stress of the key forage legume species alfalfa (Medicago sativa) was investigated here by comparing the transcriptomes of the two cultivars Dryland (DL) and Sundory (SD), which differed with respect to their ability to tolerate salinity stress. When challenged by the stress, DL plants were better able than SD ones to scavenge reactive oxygen species. A large number of genes encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 44 publications
(38 reference statements)
1
29
0
Order By: Relevance
“…The ribosomal proteins identified in this study will make viable candidates to study their involvement in abiotic stress tolerance. The role of MYB and MYB-related TFs in salinity stress tolerance has been studied in numerous plants including grasses like alfalfa 31 and food crops like maize 32 . LYR motif containing proteins along with NADH-ubiquinone oxidoreductase are components of the mitochondrial complex I, the first complex in the respiratory chain.…”
Section: Discussionmentioning
confidence: 99%
“…The ribosomal proteins identified in this study will make viable candidates to study their involvement in abiotic stress tolerance. The role of MYB and MYB-related TFs in salinity stress tolerance has been studied in numerous plants including grasses like alfalfa 31 and food crops like maize 32 . LYR motif containing proteins along with NADH-ubiquinone oxidoreductase are components of the mitochondrial complex I, the first complex in the respiratory chain.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, CNSV had not been found in alfalfa. CNSV sequences were identified in three NCBI accessions/datasets ( SRR7751381 , SRR7751384 and SRR7751386 ) generated from alfalfa plants by third parties using the Illumina HiSeq platform ( Dong et al, 2018 ; Jiang et al, 2019b ). The assembled virus had a bipartite (RNA1 and RNA2 segments) single-stranded positive-sense RNA genome that appeared to be coding-complete.…”
Section: Alfalfa Viruses Found In Public Repositoriesmentioning
confidence: 99%
“…Prior to the work of Jiang et al (2019a) , CVX had not been identified in alfalfa. CVX-related reads were detected in alfalfa transcriptome dataset SRR7751381, BioProject PRJNA487676 ( Dong et al, 2018 ). The raw reads were assembled de novo into a coding-complete genome consisting of a single molecule of linear ssRNA of 6,603 nucleotides in length, excluding the poly(A) tail.…”
Section: Alfalfa Viruses Found In Public Repositoriesmentioning
confidence: 99%
“…For example, plant hormones, such as abscisic acid (ABA), auxin and ethylene, could function as essential endogenous signal molecules and regulate plant development and tolerance to salinity 13,14 . The WRKY and MYB transcription factors are important to the regulation of transcriptional reprogramming involved in abiotic stress responses 15,16 , which have been demonstrated to regulate the contents of chlorophyll, proline, soluble sugar as well as activities of superoxide dismutase (SOD), and catalase (CAT) under saline stress 17,18 . In response to saline stress, metabolism of unsaturated fatty acid was activated to produce various compounds, which then function as signal molecules or participate in plant defense system as antimicrobial substances [19][20][21] .…”
mentioning
confidence: 99%